2004
DOI: 10.1111/j.1651-2227.2004.tb02959.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal predictors of subcutaneous fat in the term newborn

Abstract: Aim: To determine the relative influences of some maternal factors on skinfold thickness. The effects of age, parity, height, body mass index (BMI) and pregnancy weight gain (PWG) of the mother on the subscapular skinfold thickness (SST) of the newborn were estimated, and compared with their effects on birthweight (BW), crown‐heel length (CHL) and head circumference (HC). Methods: A sample of 13, 972 healthy, term singletons was selected at the Clamart Maternity Hospital (France). Stepwise regressions were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
3
15
0
1
Order By: Relevance
“…This nutritional status is determined by genetics, gender, environmental factors and especially by gestational age (GA) (Catalano and Kirwan 2001;Guihard-Costa et al 2004;Henriksen 2006). In fact, weight variations related to GA and gender have allowed the identification of newborns at perinatal risk (Lubchenco et al 1972;Clayton et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This nutritional status is determined by genetics, gender, environmental factors and especially by gestational age (GA) (Catalano and Kirwan 2001;Guihard-Costa et al 2004;Henriksen 2006). In fact, weight variations related to GA and gender have allowed the identification of newborns at perinatal risk (Lubchenco et al 1972;Clayton et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…1 Determinants of body composition at birth are numerous and include measures relating to both fat and skeletal size, and lean tissue. 2 Studies have shown a positive association between birth weight and body mass index (BMI) in children and adolescents with both the prenatal environment 3 and maternal factors 4 having lifelong consequences for obesity however, little is known about the predictors of neonatal adiposity and their role in the development of obesityrelated outcomes in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Such factors include maternal BMI just before pregnancy and weight gain during pregnancy, gender, parity, alcohol consumption and smoking during pregnancy. 2,12 The mechanisms by which these factors interact with each other remain undetermined. Skinfold thickness measurements along with data on placental weight from a large cohort of women and their offspring have not been available in many cohorts to date thus, this study provided us with the opportunity to examine prenatal maternal factors associated with neonatal adiposity and to explore the respective role of birth and placental weight as potential mediators in such associations using data from the Tasmanian Infant Health Survey (TIHS).…”
Section: Introductionmentioning
confidence: 99%
“…Aunque no contamos con la variable ganancia ponderal en este estudio, para realizar el análisis correspondiente de la contribución de esta variable, se ha demostrado que las mujeres multíparas presentan mayor índice de masa corporal que las nulíparas, debido a mayor ganancia ponderal en cada embarazo y aumentan de peso conforme aumentan en edad ( 28,29 ).…”
Section: Resultsunclassified